Lessons learned spanning 17 years of experience with three consecutive nationwide competency based medical education training plans - de Heer, Merel H.; Driessen, Erik W.; Teunissen, Pim W.; Scheele, Fedde (Frontiers in Medicine, 2024)
Introduction: Curricula for postgraduate medical education have transformed since the introduction of competency based medical education (CBME). Postgraduate training plans offer broader training with different competencies and an outcome-based approach, in addition to the medical technical aspects of training. However, CBME also has its challenges. Over the past years, critical views have been shared on the potential drawbacks of CBME, such as assessment burden and conflicts with practicality in the workplace. Recent studies identified a need for a better understanding of how the evolving concept of CBME has been translated to curriculum design and implemented in the practice of postgraduate training. The aim of this study was to describe the development of CBME translations to curriculum design, based on three consecutive postgraduate training programs spanning 17 years.Method: We performed a document analysis of three consecutive Dutch gynecology and obstetrics training plans that were implemented in 2005, 2013 and 2021.We used template analysis to identify changes over time.Results: Over time, CBME-based curriculum design changed in several domains. Assessment changed from a model with a focus on summative decision to one with an emphasis on formative, low-stakes assessments aimed at supporting learning. The training plans evolved in parallel to evolving educational insights, e.g. by placing increasing emphasis on personal development. The curricula focused on a competency-based concept by introducing training modules and personalized authorization based on feedback rather than on a set duration of internships. There was increasing freedom in personalized training trajectories in the training plans, together with increasing trust towards the resident.The way CBME was translated into training plans has evolved in the course of 17 years of experience with CMBE-based education. The main areas of change were the structure of the training plans, which became increasingly open, the degree to which learning outcomes were mandatory or not, and the way these outcomes were assessed.